Quantum Cascade Laser-Based Photoacoustic Sensor for Trace Detection of Formaldehyde Gas - Elia, Angela (Molecular Diversity Preservation International (MDPI), 2009)
We report on the development of a photoacoustic sensor for the detection of formaldehyde (CH(2)O) using a thermoelectrically cooled distributed-feedback quantum cascade laser operating in pulsed mode at 5.6 μm. A resonant photoacoustic cell, equipped with four electret microphones, is excited in its first longitudinal mode at 1,380 Hz. The absorption line at 1,778.9 cm(−1) is selected for CH(2)O detection. A detection limit of 150 parts per billion in volume in nitrogen is achieved using a 10 seconds time constant and 4 mW laser power. Measurements in ambient air will require water vapour filters.